Pulse current assisted regulation for creep aging behavior of 1420 alloy under different current density - Yuan Liu; Minghao Li; Guoqing Chen; Yufei Zu; Wenlong Zhou; Xuesong Fu (Journal of Materials Research and Technology)
Creep Age Forming (CAF), as a contemporary alloy forming method which integrates heat treatment strengthening with the forming manufacturing process, has been employed to manufacture large integral panel components with high-performance and precise. Even so, the efficiency and accuracy of CAF can be further improved via introduction of electric pulse during the production. In this study, the creep aging behavior of the 1420 Al–Li–Mg–Zr alloy through electric pulse creep aging (ECA) and conventional creep aging (CCA) processes across varying temperatures had been investigated. The results highlight the significant impact of electrical pulses on creep properties, mechanical traits, and microstructural evolution during creep aging. ECA samples demonstrate 1.65 to 2.48 times higher creep strain compared to CCA samples at different temperature. The introduction of electrical pulses curtails the activation energy (Q) of the alloy from 93.129 to 86.773 kJ mol⁻1. Furthermore, dislocation density, assessed using the Williamson–Hall method, and dimensions of the δ′ phase (Al3Li), determined by Nano Measurer 1.2 software from transmission electron microscopy images, are found higher in ECA samples at the same temperature, contributing to enhanced yield strength. Calculations identify order hardening as the primary strengthening mechanism, complemented by dislocation strengthening in creep-aged alloy, aligning with expectations.